PENGGUNAAN STRATEGI MIND MAPPING DALAM PEMBELAJARAN KOSAKATA BAHASA ARAB - Shofwatul Fu'adah (Fakultas Tarbiyah Universitas Ibrahimy, 2021)
For muslims, Arabic language is more important than the other languages. One of the ways to understand Arabic is learn about it. Learning strategies have an important role in learning Arabic, including learning vocabulary. But, in reality Many students feel difficult to learn Arabic, especially in mastering mufradat and other materials. One of the reasons is the wrong process when studying mufradat. This paper describes the implementation of mind mapping strategy in learning Arabic vocabulary at Junior High School (SMP) Alam Banyuwangi. This study used a descriptive qualitative approach with three data collection techniques, namely observation, interviews, and documentation. The results showed that mind mapping strategy can help the teachers to solve the problem of learning Arabic, especially to improve students' mastery of Arabic vocabulary. Because mind maps use visual and sensory reminders in a pattern of related ideas. This map evokes original ideas and triggers memories easily.